Peculiarities of Determination of Electromagnetic Interference Emission from Electric Propulsion Thrusters under Ground Conditions. (2017) - Arbatskiy, V.M.; Baranov, S.V.; Vazhenin, N.A.; Plokhikh, A.P.; Popov, G.A.
Abstract: The paper is devoted to analysis and methodological generalization of the available methods used to determine self emission of electric propulsion thrusters in the radio-frequency range that may represent interference for the "Earth-spacecraft" channel of the space communication systems. Peculiarities of the EP self-emission determination are discussed by the example of the measuring facility developed by RIAME MAI, and measurement results are presented. Frequency distribution of the electric field intensity within the frequency range of 1-18 GHz for the vertical and horizontal polarizations of the received signal was considered as the primary measurement parameter. Comparative analysis was made for the data obtained by measuring the EP self-emission using the developed measuring facility and the use of metal vacuum chambers.